2009
DOI: 10.1177/026010600902000105
|View full text |Cite
|
Sign up to set email alerts
|

Fish Oil and the Management of Hypertriglyceridemia

Abstract: Hypertriglyceridemia, regarded as one of the independent clinical markers of metabolic syndrome, is a frequently observed disorder that has been shown to be common in the Arab region. Epidemiologic and clinical trials demonstrated that omega-3 fatty acids have the potential to reduce the incidence of cardiovascular disease (CVD); one of the mechanisms by which this effect is achieved is through reducing plasma triglyceride levels. There is strong scientific evidence from human trials that omega-3 fatty acids f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 37 publications
1
11
0
3
Order By: Relevance
“…Epidemiologic studies demonstrate reductions in the incidence of nonfatal myocardial infarction and ischemic stroke [48]. There is variation in the effects of omega oils, however an individual’s responsiveness to fish oil could be attributed to his/her ApoE genotype [49]. Small studies have shown fish oils help to slightly lower blood pressure as well as having anti-arrhythmic properties [50-53].…”
Section: Lifestyle Modification or Non Pharmacological Management Of mentioning
confidence: 99%
“…Epidemiologic studies demonstrate reductions in the incidence of nonfatal myocardial infarction and ischemic stroke [48]. There is variation in the effects of omega oils, however an individual’s responsiveness to fish oil could be attributed to his/her ApoE genotype [49]. Small studies have shown fish oils help to slightly lower blood pressure as well as having anti-arrhythmic properties [50-53].…”
Section: Lifestyle Modification or Non Pharmacological Management Of mentioning
confidence: 99%
“…Marine-derived omega 3 (n À 3) fatty acids, including eicosapentaenoic (20 : 5n À 3, EPA) and docosahexaenoic acid (22 : 6n À 3, DHA) have been repeatedly demonstrated to reduce circulating TAG concentrations with an associated increase in LDL-C in the range of 5-10% [14]. However, the LDL-C-raising response to fish oil consumption has a significant degree of interindividual variability [6].…”
Section: Marine-based and Plant-based Omega-3 Fatty Acidsmentioning
confidence: 99%
“…For instance, patients with hypertriglyceridemia have been shown to successfully respond to the use of omega-3 fatty acids even when used in conjunction with statins, with a consequence of an improvement in the lipid profile greater than with statins alone [1].…”
Section: Introductionmentioning
confidence: 99%